Cambio diacrónico en la familia lingüística yucatecana - Hofling, Charles Andrew (El Colegio de México, A.C., 2018)
This study presents a sketch of the history of the languages of the Yucatecan branch and how the linguistic differences of the current languages reflect their histories. Based on a comparative study, one may trace the differences in phonology and morphosyntax that developed in each language since the Proto-Yucatecan of 950 CE. Innovations among members of the branch are shown, which reflect separations of groups, including migrations, mostly from the north to the south. Also evidence, principally lexical evidence, is shown of contacts of members of the branch with one another and with speakers of Ch’olan languages. The result is that each language of the branch has unique characteristics and shared characteristics, which reflect their distinct histories.